Population Change and Its Consequences: India’s Concern In the 21st Century - Ghosh, Biswajit (2011)
The escalating problem of population explosion in India and the deleterious consequences of such growth on the quality of our life have now been widely recognized. Although human resource is considered very significant in the contemporary world, any sustainable society also requires an optimum population to realize the goals of equity and efficiency. Population is a pre-requisite to development only to the extent that a society requires more manpower to implement its developmental activities. But where this is not the case, as in India, excess manpower is a liability to development. This paper, based on an analysis of contemporary issues, tries to introspect into the population-environment-development debate with particular reference to India today.